Modelo de referência para cidades resilientes - Moura, Juliano Bertolotti (2021)
The objective of the research developed in this dissertation is to present a reference model for resilient cities, through short, medium and long term actions. To this end, this research was based on a medium-sized city in the state of Paraná, the city of Maringá. The proposed methodology started with a diagnostic stage, carried out using a Maturity Model, adapted from the literature specifically for this purpose. According to the identified maturity stage, a Reference Model for Resilient Cities was developed in order to promote interaction between government agencies and the population. The resulting Reference Model consists of an unprecedented set of actions to achieve resilience in an increasing way, with the first actions aimed at establishing a people and knowledge base so that future actions are developed efficiently. The guidelines presented in the Reference Model contribute in the scientific field to the management of risks and disasters and, in the social field to the consolidation of sustainable cities.